Quantum coherence in photo-ionisation with tailored XUV pulses. (28th November 2017) - Carlström, Stefanos; Mauritsson, Johan; Schafer, Kenneth J; L'Huillier, Anne; Gisselbrecht, Mathieu
Abstract: Ionisation with ultrashort pulses in the extreme ultraviolet (XUV) regime can be used to prepare an ion in a superposition of spin–orbit substates. In this work, we study the coherence properties of such a superposition, created by ionising xenon atoms using two phase-locked XUV pulses at different frequencies. In general, if the duration of the driving pulse exceeds the quantum beat period, dephasing will occur. If however, the frequency difference of the two pulses matches the spin–orbit splitting, the coherence can be efficiently increased and dephasing does not occur.